CXCR2 Ligands and mTOR Activation Enhance Reprogramming of Human Somatic Cells to Pluripotent Stem Cells - Lee, Seung-Jin; Kang, Ka-Won; Kim, Ji-Hea; Lee, Byung-Hyun; Jung, Ji-Hye; Park, Yong; Hong, Soon-Cheol; Kim, Byung-Soo (Stem cells and development, 2020)
Induced pluripotent stem cell (iPSC) technology has great promise in regenerative medicine and disease modeling. In this study, we show that human placenta-derived cell conditioned medium stimulates chemokine (C-X-C motif) receptor 2 (CXCR2) in human somatic cells ectopically expressing the pluripotency-associated transcription factors , , , and (OSKM), leading to mechanistic target of rapamycin (mTOR) activation. This causes an increase in endogenous cMYC levels and a decrease in autophagy, thereby enhancing the reprogramming efficiency of human somatic cells into iPSCs. These findings were reproduced when human somatic cells after OSKM transduction were cultured in a widely used reprogramming medium (mTeSR) supplemented with CXCR2 ligands interleukin-8 and growth-related oncogene α or an mTOR activator (MHY1485). To our knowledge, this is the first report demonstrating that mTOR activation in human somatic cells with ectopic OSKM expression significantly enhances the production of iPSCs. Our results support the development of convenient protocols for iPSC generation and further our understanding of somatic cell reprogramming.